Placental histopathology in sickle cell disease: A descriptive and hypothesis-generating study. (June 2020) - Malinowski, Ann Kinga; Dziegielewski, Claudia; Keating, Sarah; Parks, Tony; Kingdom, John; Shehata, Nadine; Rizov, Elyssa; D'Souza, Rohan
Abstract: Introduction: Abnormal placental development is a unifying factor amongst many adverse pregnancy outcomes (APOs) in Sickle Cell Disease (SCD). Our aim was to describe placental histopathologic findings in women with SCD and their relationship with APOs, and to explore the association between antenatal sonographic findings and placental pathology. Methods: Retrospective single-centre case series of all pregnant women with SCD (January 2000–December 2017), pregnancy beyond 20 weeks' gestation, and available placenta histopathology. APOs included intrauterine fetal death, early neonatal death, preterm birth, small for gestational age, and hypertensive disorders of pregnancy. Review of images for mid-pregnancy ultrasound and one proximal to delivery was completed, blinded to clinical outcomes and histopathology results. Gross and histopathologic findings were reviewed and characterized per published classification. Results: Of 72 placentas, abnormalities were present in 69%, with Maternal Vascular Malperfusion (MVM) noted in 40%. APOs were encountered in 61% overall and in 79% of those with MVM. Neither SCD genotype nor severe maternal anemia had an influence on histopathologic placental features. Presence of high-resistance uterine artery waveforms at mid-trimester ultrasound was strongly associated with APOs and with abnormal findings on placental histopathology, most notably MVM. MVM was strongly associated with small for gestational age infants, preterm birth, and stillbirth. Discussion: MVM is the predominant lesion in placentas of women with SCD and is strongly associated with APOs. Mid-trimester ultrasound can identify a subset of women at risk. Future research into advanced imaging modalities to aid in antenatal diagnosis alongside investigations of potentially beneficial therapies is needed. Highlights: Maternal Vascular Malperfusion is the principal lesion in placentas of women with SCD. Maternal Vascular Malperfusion is strongly associated with adverse outcomes. In SCD, high-resistance uterine artery wave-form is associated with MVM and APO. Placental abnormalities are not influenced by severe maternal anemia or SCD-genotype.